WACANA DAN GERAKAN PEREMPUAN ISLAM DI INDONESIA - Diana, MSi., Ilvi Nur (EGALITA, 2006)
Women's movement is one of important issues in the development of socio-intelectual discourse of Islam in Indonesia. Most figures emerge to encourage women in order that they pose higher possitions and get involved in public area roles, beyond their traditional roles as housewives. In line with that opinion, effort has been taken to realize the arguments that women issues are only women's bussines. Does not belong to women only, but also men's. Those issues invited moslem scientist's attention to contribute intelectually for women's empowerment and theirÂ  statusesÂ  in islamic tradition.